"Algaquaculture" integrating algae-culture with aquaculture for sustainable development. (20th January 2020) - Yang, Limin; Wang, Ruolan; Lu, Qian; Liu, Hui
Highlights: Aquaponics is a good system for sustainable aquaculture but it has serious problems. Algaquaculture is a novel concept that integrates algae culture with aquaculture. Algaquaculture is expected to perform better in nutrients recovery and economic value.